A Single-Centre 10-Year Experience with Candida Bloodstream Infections - Annie-Claude Labbé; Jacques Pépin; Carlos Patiño; Stéphanie Castonguay; Christiane Restieri; Michel Laverdiere (Canadian Journal of Infectious Diseases and Medical Microbiology)
OBJECTIVE: To describe the clinical and microbiological features associated with Candida bloodstream infections observed at Hôpital Maisonneuve-Rosemont (Montreal, Quebec) between August 1996 and July 2006.